Immediate Interventions for Presyncope of Vasovagal or Orthostatic Origin: A Systematic Review. (2nd January 2020) - Jensen, Jan L.; Ohshimo, Shinichiro; Cassan, Pascal; Meyran, Daniel; Greene, Jennifer; Ng, Kee Chong; Singletary, Eunice; Zideman, David; ,
Abstract: Background: Syncope is a common condition that may be prevented. There are non-pharmacological interventions that may be of benefit during the acute episode preceding syncope (presyncope), including physical counter-pressure maneuvers (PCM) or change of body position. We performed a systematic review of interventions that may be applied during presyncope as an immediate, first aid tactic. Methods: We searched Medline, Embase, and CINAHL and used the Grading of Recommendations Assessment, Development and Evaluation methods, and risk of bias assessments to determine the certainty of the evidence. We included randomized controlled trials (RCTs), non-randomized studies, and case series investigating adults and children with signs and symptoms of presyncope of suspected vasovagal or orthostatic origin who applied any intervention that could be used as an immediate, first aid intervention. We examined the following outcomes: prevention of syncope, adverse events, symptom improvement, and vital signs. We conducted a sub-group analysis based on the etiology of vasovagal or orthostatic presyncope. Results: We screened 5, 160 titles and abstracts followed by 81 full text articles. We identified 8 studies meeting inclusion criteria, including 2 RCTs and 6 observational studies. All studies used PCM in adults and all were judged to be of low and very low certainty of evidence. For prevention of syncope, one RCT demonstrated benefit with the use of PCM (RR = 1.80 [1.26–1.89]), while observational studies failed to show benefit (RR = 1.31 [0.98 – 1.75]). Two RCTs showed benefit in symptom improvement (RR = 6.00 [2.21 – 8.61] and (RR = 1.57 [1.06 – 1.93]). Blood pressure (BP) improved with the use of PCM: systolic BP mean difference (MD) 21 mmHg higher (95% CI: 18.25 to 23.41 BPM) and diastolic BP MD 11 mmHg higher (95% CI: 9.39 to 13.10 mmHg higher). No adverse events were reported. Conclusion: While there is a minimal amount of evidence available and the findings were mixed, PCM may provide benefit for prevention of syncope during acute episodes of presyncope and may be tried in the first aid setting. No evidence was found for other non-pharmacologic interventions or for the use of PCM in children.